2022
DOI: 10.3389/fnhum.2022.829924
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Competitive Field Hockey Match on Cognitive Function

Abstract: Despite the known positive effects of acute exercise on cognition, the effects of a competitive team sport match are unknown. In a randomized crossover design, 20 female and 17 male field hockey players (19.7 ± 1.2 years) completed a battery of cognitive tests (Visual Search, Stroop, Corsi Blocks, and Rapid Visual Information Processing) prior to, at half-time, and immediately following a competitive match (or control trial of seated rest); with effect sizes (ES) presented as raw ES from mixed effect models. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Three studies showed that CTSB levels did not change after chronic and acute exercise: Gourgouvelis et al (2018) demonstrated that eight weeks of exercise did not change plasma CTSB levels in young adults, and Nicolini et al (2019) demonstrated that 6 weeks of HIIT did not change serum CTSB levels in young males. Malcolm et al (2022) demonstrated that acute field hockey match did not change plasma CTSB levels in young athletes.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Three studies showed that CTSB levels did not change after chronic and acute exercise: Gourgouvelis et al (2018) demonstrated that eight weeks of exercise did not change plasma CTSB levels in young adults, and Nicolini et al (2019) demonstrated that 6 weeks of HIIT did not change serum CTSB levels in young males. Malcolm et al (2022) demonstrated that acute field hockey match did not change plasma CTSB levels in young athletes.…”
Section: Resultsmentioning
confidence: 86%
“…All eight included studies were published between 2016–2022 and had been conducted in six countries (Canada: 2, Poland:1, Spain:1, Turkey:1, UK: 1, USA: 2). Six studies used experimental designs (Gaitán et al, 2021; Gourgouvelis et al, 2018; Micielska et al, 2021; Moon et al, 2016; Nicolini et al, 2019 Malcolm et al, 2022), one study had a cross-sectional design (De la Rosa et al, 2019), and one study had both cross-sectional and experimental sections (Gokce et al, 2021). The sample size ranged from 18 to 68 participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations